Case Study and Policy Analysis in Enhancing Midwifery Students' Understanding of the International Code of Marketing of Breastmilk Substitutes - Ambarwati, Kusmayra; Hidayana, Irma (Global Education Journal, 2025)
Background: The International Code of Marketing of Breastmilk Substitutes (the Code), adopted by the World Health Assembly in 1981, remains a cornerstone in protecting breastfeeding from inappropriate commercial influence. Purpos of study: This study aims to evaluate the combined use of case study and policy analysis methods in enhancing midwifery students’ understanding of the Code. Methods: This qualitative study applied a dual-method approach case study and policy analysis to enhance student understanding of the Code within the context of Indonesia. Case reports of Code violations were documented by midwifery students through field assignments, while a policy analysis component utilized lecture materials, government regulations (PP 33/2012; Ministry of Health regulation 39/2013), and WHO/UNICEF guidance. Results: Findings demonstrate that combining case-based learning with structured policy analysis significantly improved students’ ability to identify Code breaches, link them to specific articles, and recommend appropriate reporting and advocacy measures. This approach not only strengthened academic learning but also fostered professional advocacy skills. Conclusion: The study concludes that integrating case study and policy analysis into midwifery curricula can be an effective pedagogical model to prepare health professionals as protectors of breastfeeding rights in line with international and national commitments.